Crystalline form D of OAB-14 and preparation method thereof

By developing the crystal form D of OAB-14, the problems of limited efficacy and major side effects of existing AD treatment drugs have been solved, and the effective and multi-target therapeutic effects have been achieved, and the stability and bioavailability of the drug have been improved.

CN119219527BActive Publication Date: 2025-03-11SHANDONG XINHUA PHARMA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411754653.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The prior art has limited efficacy in the treatment of Alzheimer's disease, and the drug's mechanism of action is single, with many side effects. It is necessary to develop new, efficient, multi-target AD therapeutic drugs.

Method used

A new drug, OAB-14, has been developed and the crystal form D, which is prepared by suspending beating at a suitable solvent and temperature, combined with suction filtration and drying steps, and achieves high crystallinity, anhydrous form, high dissolution and high stability.

Benefits of technology

The crystal form D of OAB-14 significantly improves the solubility, stability and bioavailability of the drug, enhances the efficacy of treating Alzheimer's disease, and reduces side effects, with significant development potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219527B_ABST
    Figure CN119219527B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of OAB-14 pharmaceutical chemistry and preparation technology, and specifically relates to a crystal form D of OAB-14 and a preparation method thereof. The preparation method of the crystal form D of OAB-14 described in the present invention is as follows: OAB-14 is added to a solvent, suspended and slurried, kept warm and stirred, filtered, and dried to obtain a crystal form D. The solvent is one of THF (tetrahydrofuran), MeOH (methanol), EtOH (methanol), EA (ethyl acetate), and MTBE (methyl tert-butyl ether). The suspension and slurrying temperature is 15 to 25°C. The time for the insulation and stirring is 1 to 5 days. After the OAB-14 is added to the solvent, the concentration of OAB-14 is 0.005 g / mL to 0.01 g / mL. The preparation method of the crystal form D of OAB-14 provided by the present invention, the crystal form D is a high crystallinity, anhydrous crystal form, high solubility, and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of OAB-14 pharmaceutical chemistry and preparation technology thereof, and specifically relates to a crystal form D of OAB-14 and a preparation method thereof. Background Art

[0002] Alzheimer's disease (AD) is a serious neurodegenerative disease, which is mainly manifested by progressive cognitive impairment, including disorders in memory, language, calculation, visual-spatial function and judgment, which seriously affect patients' daily life and social activities. With the acceleration of the global aging process, the incidence of AD has increased year by year and has become a major public health issue. At present, although there are many drugs for the treatment of AD, their efficacy is limited, and most drugs have a single mechanism of action, mainly focusing on cholinesterase inhibitors and N-methyl-D-aspartate (NMDA) receptor antagonists. However, these drugs cannot effectively prevent the progression of AD and have many side effects. Therefore, it is particularly important to develop new, efficient and multi-target AD therapeutic drugs.

[0003] OAB-14 is a new class of drugs independently developed, and its structural formula is: , intended for the treatment of Alzheimer's disease. Preliminary studies have shown that OAB-14 can significantly improve a variety of behavioral disorders such as learning, memory, and social activities in APP / PS1 double transgenic AD model mice. This therapeutic effect is significantly different from the targets and mechanisms of existing AD therapeutic drugs, and is also significantly different from the targets and mechanisms of most anti-AD drugs that have failed in clinical trials. The anti-AD mechanism of action of OAB-14 is complex and diverse. In addition to being related to the clearance of beta-amyloid protein (Aβ) deposits in the brain, it also involves multi-target mechanisms such as central anti-inflammatory, anti-oxidation, and inhibition of neuronal apoptosis. These characteristics give OAB-14 significant advantages and potential in the treatment of AD.

[0004] In the process of drug development, crystal form research is one of the important links in drug development. Different crystal forms not only affect the solubility, stability and bioavailability of drugs, but may also have an important impact on the efficacy and safety of drugs. Although the crystal forms A, B and C of OAB-14 and their preparation processes have been studied and reported in detail. However, in order to further optimize the drug properties of OAB-14 and improve the efficacy and safety of drugs, the drug properties of other crystal forms need to be further studied. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a crystalline form D of OAB-14. The crystalline form D is a high-crystallinity, anhydrous crystalline form with high solubility and high stability. The present invention also provides a method for preparing the crystalline form D.

[0006] The preparation method of the crystal form D of OAB-14 described in the present invention comprises: adding OAB-14 to a solvent, suspending and slurrying, stirring at a warm temperature, filtering, and drying to obtain the crystal form D.

[0007] The solvent is one of THF (tetrahydrofuran), MeOH (methanol), EtOH (ethanol), EA (ethyl acetate), and MTBE (methyl tert-butyl ether), preferably MeOH.

[0008] The mixing and beating temperature is 15-25°C, and the temperature is selected from 15°C, 20°C, 25°C, preferably 20°C.

[0009] The time of heat preservation and stirring is 1 to 5 days, and the time of heat preservation and stirring is selected from 1 day, 3 days, 5 days, and preferably 3 days.

[0010] After the OAB-14 is added to the solvent, the concentration of OAB-14 is 0.005 g / mL to 0.01 g / mL.

[0011] The drying temperature is 60-80° C., and the drying time is 6-8 hours.

[0012] The present invention carried out the following preparations for different crystalline forms of OAB-14 during the research and screening process:

[0013] (1) OAB-14 is subjected to gas-solid diffusion in a suitable solvent at a suitable temperature, and after a period of time, filtered and dried to obtain Form E. The solvent is acetone or acetone / water, preferably acetone; the temperature is 10°C, 15°C, 20°C, preferably 15°C; the beating time is 1 day, 3 days, 5 days, preferably 3 days.

[0014] (2) Cyclic heating and cooling of OAB-14 in a suitable solvent, suction filtration, and natural drying to obtain Form F. The solvent is DMSO or DMSO / water, preferably DMSO; the cyclic heating and cooling temperature is one of 10°C~30°C~10°C, 20°C~40°C~20°C, 30°C~50°C~30°C, preferably 20°C~40°C~20°C; the beating time is 2h, 4h, 6h, preferably 4h.

[0015] (3) Suspending and beating OAB-14 in a suitable solvent at a suitable temperature, and then cyclically heating and cooling, filtering, and drying to obtain Form G. The solvent is water; the cyclic heating and cooling temperature is one of 20°C~40°C~20°C, 30°C~50°C~30°C, 40°C~60°C~40°C, preferably 30°C~50°C~30°C; the beating time is 3 days, 5 days, 7 days, preferably 5 days.

[0016] (4) Suspending and beating OAB-14 in a suitable solvent, and then cyclically heating and cooling, filtering, and drying to obtain Form H. The solvent is N,N-dimethylformamide; the cyclic heating and cooling temperature is one of 20°C~40°C~20°C, 30°C~50°C~30°C, 40°C~60°C~40°C, preferably 30°C~50°C~30°C; the beating time is 5 days, 7 days, 9 days, preferably 7 days.

[0017] (5) OAB-14 is suspended and slurried in a suitable solvent, and then subjected to cyclic heating and cooling, suction filtration, and drying to obtain Form I. The solvent is N-methylpyrrolidone; the cyclic heating and cooling temperature is one of 30°C~40°C~30°C, 40°C~50°C~40°C, 50°C~60°C~50°C, preferably 40°C~50°C~40°C; the slurrying time is 3 days, 5 days, 7 days, preferably 5 days.

[0018] (6) Form J can be obtained by heating Form W under nitrogen protection and maintaining for a period of time. The heating temperature is one of 200°C, 250°C, and 300°C, preferably 250°C; the heating time is one of 5 min, 10 min, and 15 min, preferably 10 min.

[0019] (7) Form K can be obtained by heating Form L under nitrogen protection and maintaining for a period of time. The heating temperature is one of 200°C, 250°C, and 300°C, preferably 250°C; the heating time is one of 5 min, 10 min, and 15 min, preferably 10 min.

[0020] (8) Suspending and beating OAB-14 in a suitable solvent at a suitable temperature, filtering after a period of time, and drying to obtain Form L. The solvent is acetone; the temperature is 0°C, 5°C, 10°C, preferably 5°C; the beating time is 3 days, 5 days, 7 days, preferably 5 days.

[0021] (9) Suspending and beating OAB-14 in a suitable solvent at a suitable temperature, filtering after a period of time, and drying to obtain Form M. The solvent is butanone; the temperature is 0°C, 5°C, 10°C, preferably 5°C; the beating time is 5 days, 7 days, 9 days, preferably 7 days.

[0022] (10) Suspending and beating OAB-14 in a suitable solvent at a suitable temperature, filtering after a period of time, and drying to obtain Form N. The solvent is acetonitrile; the temperature is 0°C, 5°C, 10°C, preferably 5°C; the beating time is 5 days, 7 days, 9 days, preferably 7 days.

[0023] (11) Suspending and beating OAB-14 in a suitable solvent at a suitable temperature, filtering and drying after a period of time to obtain Form O. The solvent is dimethyl sulfoxide; the temperature is 100°C, 120°C, 140°C, preferably 120°C; the beating time is 1 day, 3 days, 5 days, preferably 3 days.

[0024] (12) OAB-14 is subjected to gas-solid diffusion in a suitable solvent at a suitable temperature, and after a period of time, filtered and dried to obtain the crystal form P. The solvent is N-methylpyrrolidone; the temperature is 0°C, 5°C, 10°C, preferably 5°C; the beating time is 5 days, 7 days, 9 days, preferably 7 days.

[0025] (13) OAB-14 is suspended and slurried in a suitable solvent at a suitable temperature, and after a period of time, filtered and dried to obtain Form Q. The solvent is 2-methyltetrahydrofuran; the temperature is 20°C, 40°C, 60°C, preferably 40°C; the slurrying time is 5 days, 7 days, 9 days, preferably 7 days.

[0026] (14) OAB-14 is suspended and slurried in a suitable solvent at a suitable temperature, and after a period of time, filtered and dried to obtain Form R. The solvent is butanone; the temperature is 40°C, 50°C, 60°C, preferably 50°C; and the slurrying time is 1 day, 3 days, 5 days, preferably 3 days.

[0027] (15) Dissolve OAB-14 in a suitable solvent, evaporate at a certain temperature to precipitate a solid, filter it, and dry it to obtain Form S. The solvent is methanol; the temperature is 15°C, 20°C, 25°C, preferably 25°C;

[0028] (16) Dissolve OAB-14 in a suitable solvent, evaporate rapidly to precipitate a solid, filter, and dry to obtain Form T. The solvent is methanol / dichloromethane in a volume ratio of 1:1; the temperature is 40°C, 50°C, 60°C, preferably 50°C;

[0029] (17) Dissolve OAB-14 in a suitable solvent, evaporate at a certain temperature to precipitate a solid, filter it, and dry it to obtain Form U. The solvent is ethanol; the temperature is 15°C, 20°C, 25°C, preferably 20°C;

[0030] (18) OAB-14 is dissolved in a suitable solvent, volatilized at a certain temperature to precipitate a solid, filtered, and dried to obtain Form V. The solvent is acetonitrile / water; the temperature is 15°C, 20°C, 25°C, preferably 20°C; the volume ratio of acetonitrile / water is one of 2:1, 4:1, and 6:1, preferably 4:1.

[0031] (19) OAB-14 is dissolved in a suitable solvent, and solid is precipitated after rapid volatilization, filtered, and dried to obtain Form W. The solvent is acetone / water; the temperature is 40° C., 50° C., 60° C., preferably 50° C.; the volume ratio of acetone / water is one of 3:1, 4:1, and 5:1, preferably 4:1.

[0032] (20) Dissolve OAB-14 in a suitable solvent, evaporate rapidly to precipitate a solid, filter, and dry to obtain Form X. The solvent is ethanol; the temperature is 50°C, 60°C, 70°C, preferably 60°C;

[0033] (21) Dissolve OAB-14 in a suitable solvent, cool rapidly to precipitate solid, filter, and dry to obtain Form Y. The solvent is acetone / water; the dissolution temperature is one of 50°C, 60°C, and 70°C, preferably 60°C. The cooling rate is 5°C / min, 10°C / min, 15°C / min, preferably 10°C; the acetone / water volume ratio is one of 3:1, 4:1, and 5:1, preferably 4:1.

[0034] (22) Form Z can be obtained by placing Form B under illumination (cold white light, 5000 Lux ± 500 Lux; closed) for 3 days, 5 days, 7 days, preferably 5 days.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The preparation method of the crystal form D of OAB-14 of the present invention only requires suspending and slurrying OAB-14 in a suitable solvent and temperature, and after a period of reaction, it can be obtained through simple filtration and drying steps. This preparation process does not require complicated equipment and operations, reduces production costs, and improves production efficiency.

[0037] (2) The crystal form D of OAB-14 prepared by the method of the present invention has good physicochemical stability. This crystal form has potential application value in subsequent drug development research and can ensure the stability and effectiveness of the drug during storage and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is the XRPD pattern of Form A;

[0039] Figure 2 It is the DSC and TGA superposition spectrum of Form A;

[0040] Figure 3 It is the crystal form A 1 H-NMR spectrum;

[0041] Figure 4is the XRPD pattern of Form B;

[0042] Figure 5 It is the DSC and TGA superposition spectrum of Form B;

[0043] Figure 6 It is the crystal form B 1 H-NMR spectrum;

[0044] Figure 7 is the XRPD pattern of Form C;

[0045] Figure 8 It is the DSC and TGA superposition spectrum of Form C;

[0046] Fig. 9 It is the crystal form C 1 H-NMR spectrum;

[0047] Fig.10 is the XRPD pattern of Form D prepared in Example 2;

[0048] Fig.11 is the DSC and TGA superposition spectrum of Form D prepared in Example 2;

[0049] Fig.12 It is the crystalline form D prepared in Example 2 1 H-NMR spectrum;

[0050] Fig.13 is the XRPD comparison spectrum of Form D prepared in Example 2 and after heating respectively;

[0051] Fig.14 This is the XRPD pattern of Form E prepared in Comparative Example 1;

[0052] Fig.15 This is the DSC and TGA superposition spectrum of Form E prepared in Comparative Example 1;

[0053] Fig.16 The crystal form E prepared in Comparative Example 1 1 H-NMR spectrum;

[0054] Fig.17 This is the XRPD comparison spectrum of Form E prepared in Comparative Example 1 and its respective heating results;

[0055] Fig.18 This is the XRPD pattern of Form F prepared in Comparative Example 5;

[0056] Fig.19 The crystal form F prepared in Comparative Example 5 1 H-NMR spectrum;

[0057] Fig. 20The XRPD patterns of the crystal form F and the crystal form O prepared in Comparative Example 5 are shown in FIG.

[0058] Fig.21 This is the XRPD pattern of Form G prepared in Comparative Example 8;

[0059] Fig. 22 This is the XRPD comparison spectrum of the wet sample, dry sample and the sample after heating to 100° C. of Form G prepared in Comparative Example 8;

[0060] Fig.23 This is the DSC and TGA superposition spectrum of Form G prepared in Comparative Example 8;

[0061] Fig.24 The crystal form G prepared in Comparative Example 8 1 H-NMR spectrum;

[0062] Fig.25 This is the XRPD pattern of Form H prepared in Comparative Example 11;

[0063] Fig.26 This is the DSC and TGA superposition spectrum of Form H prepared in Comparative Example 11;

[0064] Fig. 27 The crystal form H prepared in Comparative Example 11 1 H-NMR spectrum;

[0065] Fig.28 This is the XRPD pattern of Form I prepared in Comparative Example 14;

[0066] Fig.29 This is the DSC and TGA superposition spectrum of Form I prepared in Comparative Example 14;

[0067] Fig.30 The crystal form I prepared in Comparative Example 14 1 H-NMR spectrum;

[0068] Fig.31 This is the XRPD comparison spectrum of Form I prepared in Comparative Example 14 and after heating;

[0069] Fig.32 is the XRPD spectrum of Form J prepared in Comparative Example 17;

[0070] Fig.33 is the XRPD spectrum of Form K prepared in Comparative Example 20;

[0071] Fig.34 The crystal form K prepared in Comparative Example 20 1 H-NMR spectrum;

[0072] Fig.35 This is the XRPD pattern of Form L prepared in Comparative Example 23;

[0073] Fig.36 This is the DSC and TGA superposition spectrum of Form L prepared in Comparative Example 23;

[0074] Fig.37 The crystal form L prepared in Comparative Example 23 1 H-NMR spectrum;

[0075] Fig.38 This is the XRPD comparison spectrum of Form L prepared in Comparative Example 23 and its heated form;

[0076] Fig.39 is the XRPD spectrum of Form M prepared in Comparative Example 26;

[0077] Fig.40 is the DSC and TGA superimposed spectrum of Form M prepared in Comparative Example 26;

[0078] Fig.41 The crystal form M prepared in Comparative Example 26 1 H-NMR spectrum;

[0079] Fig.42 is the XRPD spectrum of Form N prepared in Comparative Example 29;

[0080] Fig.43 is the DSC and TGA superimposed spectrum of Form N prepared in Comparative Example 29;

[0081] Fig.44 The crystal form N prepared in Comparative Example 29 1 H-NMR spectrum;

[0082] Fig.45 This is a comparison of XRPD spectra of Form N prepared in Comparative Example 29 before and after heating;

[0083] Fig.46 is the XRPD spectrum of Form O prepared in Comparative Example 32;

[0084] Fig.47 This is the DSC and TGA superposition spectrum of Form O prepared in Comparative Example 32;

[0085] Fig.48 The crystal form O prepared in comparative example 32 1 H-NMR spectrum;

[0086] Fig.49 is the XRPD pattern of Form P prepared in Comparative Example 35;

[0087] Fig.50 This is the DSC and TGA superposition of the crystal form P prepared in Comparative Example 35

[0088] Fig.51 The crystal form P prepared in Comparative Example 35 1 H-NMR spectrum;

[0089] Fig.52 is the XRPD spectrum of Form Q prepared in Comparative Example 38;

[0090] Fig.53 is the DSC and TGA superimposed spectrum of Form Q prepared in Comparative Example 38;

[0091] Fig.54 The crystal form Q prepared in Comparative Example 38 1 H-NMR spectrum;

[0092] Fig.55 is the XRPD spectrum of Form R prepared in Comparative Example 41;

[0093] Fig.56 is the DSC and TGA superimposed spectrum of Form R prepared in Comparative Example 41;

[0094] Fig.57 The crystal form R prepared in Comparative Example 41 1 H-NMR spectrum;

[0095] Fig.58 This is a comparison of XRPD spectra of Form R prepared in Comparative Example 41 before and after heating;

[0096] Fig.59 is the XRPD spectrum of Form S prepared in Comparative Example 44;

[0097] Fig.60 is the DSC and TGA superimposed spectrum of Form S prepared in Comparative Example 44;

[0098] Fig.61 The crystal form S prepared in Comparative Example 44 1 H-NMR spectrum;

[0099] Fig.62 is the XRPD spectrum of Form T prepared in Comparative Example 47;

[0100] Fig.63 is the DSC and TGA superimposed spectrum of Form T prepared in Comparative Example 47;

[0101] Fig.64 The crystal form T prepared in Comparative Example 47 1 H-NMR spectrum;

[0102] Fig.65 is the XRPD spectrum of Form U prepared in Comparative Example 50;

[0103] Fig.66This is the DSC and TGA superposition spectrum of Form U prepared in Comparative Example 50;

[0104] Fig.67 The crystal form U prepared in Comparative Example 50 1 H-NMR spectrum;

[0105] Fig.68 is the XRPD spectrum of Form V prepared in Comparative Example 53;

[0106] Fig.69 is the XRPD spectrum of Form W prepared in Comparative Example 56;

[0107] Fig.70 is the DSC and TGA superimposed spectrum of Form W prepared in Comparative Example 56;

[0108] Fig.71 The crystal form W prepared in Comparative Example 56 1 H-NMR spectrum;

[0109] Fig.72 This is the XRPD comparison spectrum of Form W prepared in Comparative Example 56 and after heating;

[0110] Fig.73 is the XRPD spectrum of Form X prepared in Comparative Example 59;

[0111] Fig.74 is the XRPD spectrum of Form Y prepared in Comparative Example 62;

[0112] Fig.75 is the DSC and TGA superimposed spectrum of Form Y prepared in Comparative Example 62;

[0113] Fig.76 The crystal form Y prepared in Comparative Example 62 1 H-NMR spectrum;

[0114] Fig.77 is the XRPD spectrum of Form Z prepared in Comparative Example 65;

[0115] Fig.78 is the DSC and TGA superimposed spectrum of Form Z prepared in Comparative Example 65;

[0116] Fig.79 The crystal form Z prepared in comparative example 65 1 H-NMR spectrum;

[0117] Fig.80 DVS spectrum of Form A;

[0118] Fig.81 XRPD comparison patterns of Form A before and after DVS testing;

[0119] Fig.82 DVS spectrum of Form B;

[0120] Fig.83 XRPD comparison patterns of Form B before and after DVS testing;

[0121] Fig.84 DVS spectrum of Form C;

[0122] Fig.85 XRPD comparison patterns of Form C before and after DVS testing;

[0123] Fig.86 is the DVS spectrum of Form D prepared in Example 2;

[0124] Fig.87 is the XRPD comparison spectrum of Form D prepared in Example 2 before and after DVS test;

[0125] Fig.88 This is the DVS spectrum of the crystal form E prepared in Comparative Example 1;

[0126] Fig.89 This is the XRPD comparison spectrum of the crystal form E prepared in Comparative Example 1 before and after the DVS test;

[0127] Fig.90 XRPD comparison of the solid remaining after Form A was shaken in the medium for 24 hours;

[0128] Fig.91 NMR comparison of the solid remaining after Form A was shaken in FaSSGF medium for 24 hours;

[0129] Fig.92 XRPD comparison of the solid remaining after Form B was shaken in the medium for 24 hours;

[0130] Fig.93 XRPD comparison of the solid remaining after Form C was shaken in the medium for 24 hours;

[0131] Fig.94 This is the XRPD comparison spectrum of the solid remaining after the crystal form D prepared in Example 2 was shaken in the medium for 24 hours;

[0132] Fig.95 This is a comparative XRPD spectrum of the solid remaining after the crystal form E prepared in comparative example 1 was shaken in the medium for 24 hours;

[0133] Fig.96 It is the XRPD pattern of the mixture of crystal forms A, B, D, E, G, L, S, T, U, and Y at different water activities.

[0134] Fig.97 XRPD overlay pattern of Form A stability sample;

[0135] Fig.98 XRPD overlay of Form B stability sample;

[0136] Fig.99 XRPD overlay of Form C stability sample;

[0137] Fig.100 is the XRPD superposition pattern of the stability sample of Form D prepared in Example 2;

[0138] Fig.101 This is the XRPD superposition spectrum of the stability sample of Form E prepared in Comparative Example 1;

[0139] Fig.102 XRPD comparison of Form A before and after grinding;

[0140] Fig.103 XRPD comparison of Form A before and after tableting;

[0141] Fig.104 XRPD comparison of Form B before and after grinding;

[0142] Fig.105 XRPD comparison of Form B before and after tableting;

[0143] Fig.106 XRPD comparison of Form C before and after grinding;

[0144] Fig.107 XRPD comparison of Form C before and after tableting;

[0145] Fig.108 is the XRPD comparison spectrum of Form D prepared in Example 2 before and after grinding;

[0146] Fig.109 is the XRPD comparison spectrum of Form D prepared in Example 2 before and after tableting;

[0147] Fig.110 This is the XRPD comparison spectrum of Form E prepared in Comparative Example 1 before and after grinding;

[0148] Fig.111 This is the XRPD comparison spectrum of Form E prepared in Comparative Example 1 before and after tableting;

[0149] Fig.112 It is the XRPD comparison pattern of the 5-day suspension competition experiment of the anhydrous crystal forms A, B, D, E, L, Y, J, and K;

[0150] Fig.113 It is the XRPD comparison pattern of the 10-day suspension competition experiment of the anhydrous crystal forms A, B, D, E, L, Y, J, and K. DETAILED DESCRIPTION

[0151] The present invention will be further described below in conjunction with specific embodiments.

[0152] The OAB-14 raw material used in the following examples is generally crystal form A, and is prepared by Shandong Xinhua Pharmaceutical Co., Ltd. The OAB-14 described is a finished product of OAB-14 with a content of 99.30%, and the batch number is Y2401308; other raw materials and reagents are normal commercial products. The crystal form A of OAB-14 described in the present invention is obtained by the preparation method described in the public patent CN113896659A, and all the examples obtained are crystal form A (batch: Y2401308); the crystal form B is obtained by the preparation method described in the public patent CN116924941A, and all the examples obtained are crystal form B (batch: QYST23-23-1); the crystal form C is obtained by the preparation method described in the public patent CN117567324A, and all the examples obtained are crystal form C (batch: Y2401306).

[0153] Example 1

[0154] The preparation method of the OAB-14 crystal form D is as follows: 0.2 g of OAB-14 is taken, 20 ml of THF is added, the mixture is suspended and slurried at 15° C., the mixture is stirred at this temperature for 1 day, the mixture is filtered, and the mixture is dried at 60° C. for 8 hours to obtain 0.19 g of OAB-14 crystal form D, with a yield of 95.0%.

[0155] Example 2

[0156] The preparation method of the OAB-14 crystal form D is as follows: 0.3 g of OAB-14 is taken, 30 ml of MeOH is added, the mixture is suspended and slurried at 20° C., the mixture is stirred at this temperature for 3 days, the mixture is filtered, and the mixture is dried at 70° C. for 7 hours to obtain 0.29 g of OAB-14 crystal form D, with a yield of 96.7%.

[0157] The obtained crystal form D was subjected to XRPD (X-ray powder diffraction), DSC (differential scanning calorimetry) and TGA (thermogravimetric analysis) superposition. 1 H-NMR (hydrogen nuclear magnetic resonance spectroscopy) comprehensive characterization, such as Figure 10~Figure 13 shown. Fig.10 The XRPD spectrum results of Form D show that the sample has a high degree of crystallinity. Fig.11 The TGA results of Form D showed that the sample lost 1.29% weight when heated from room temperature to 120.0°C, and lost 6.27% weight when further heated to 265.0°C. The sample began to decompose around 370.3°C. Fig.11 The DSC results of Form D showed that the sample had endothermic peaks near 251.2°C and 377.6°C. Fig.12Form D 1 The H-NMR results are basically consistent with those of the raw material OAB-14. In summary, Form D is an anhydrous crystalline form. Fig.13 As shown, the obtained crystal form D was heat-treated respectively, and heated to 230°C (the third line from the bottom to the top), 250°C (the fourth line from the bottom to the top), and 260°C (the second line from the bottom to the top) respectively under nitrogen protection. After the XRPD (the first line from the bottom to the top) of the crystal form D after the heat treatment was detected, it was found that Fig.13 It can be seen that the crystal form D remains unchanged after heat treatment at 230°C, changes after heating to 250°C, and transforms into crystal form J after further heating to 260°C.

[0158] The diffraction peak list of Form D of OAB-14 prepared in this example is shown in Table 1: the reflection angle 2θ of the X-ray powder diffraction pattern has characteristic peaks at 7.0252°, 9.7125°, 18.1961°, and 19.4787°, and the intensities thereof are 33.39%, 69.65%, 52.48%, and 100.00%, respectively.

[0159] Table 1 Diffraction peak list of Form D

[0160]

[0161] Example 3

[0162] The preparation method of the OAB-14 crystal form D is as follows: 0.2 g of OAB-14 is taken, 30 ml of EtOH is added, the mixture is suspended and slurried at 25° C., the mixture is stirred and kept warm for 5 days, filtered, and dried at 80° C. for 6 hours to obtain 0.18 g of OAB-14 crystal form D, with a yield of 90.0%.

[0163] Example 4

[0164] The preparation method of the OAB-14 crystal form D is as follows: 0.3 g of OAB-14 is taken, 30 ml of EA is added, the mixture is suspended and slurried at 15° C., the mixture is stirred at this temperature for 1 day, the mixture is filtered, and the mixture is dried at 60° C. for 7 hours to obtain 0.27 g of OAB-14 crystal form D, with a yield of 90.0%.

[0165] Example 5

[0166] The preparation method of the OAB-14 crystal form D is as follows: 0.1 g of OAB-14 is taken, 20 ml of MTBE is added, the mixture is suspended and slurried at 25° C., the mixture is stirred at this temperature for 5 days, the mixture is filtered, and the mixture is dried at 70° C. for 6 hours to obtain 0.08 g of OAB-14 crystal form D, with a yield of 80.0%.

[0167] The following comparative examples are obtained by other crystal forms during the screening process.

[0168] Comparative Example 1

[0169] The preparation method of the OAB-14 crystal form E is as follows: 0.2 g of OAB-14 is taken, then 20 ml of acetone is added, gas-solid diffusion is carried out at 15°C, the mixture is stirred for 3 days, filtered, and dried to obtain 0.19 g of OAB-14 crystal form E. A comprehensive characterization is performed on the crystal form E, and the results are shown in Figure 14~Figure 17 . Fig.14 The XRPD results showed that the sample had a high degree of crystallinity. Fig.15 The TGA results showed that the sample lost 1.18% weight when heated from room temperature to 100.0℃, and lost 9.29% weight when further heated to 250.0℃. The sample decomposed at around 342.3℃. Fig.15 The DSC results showed that the sample had endothermic peaks at 208.3°C and 345.1°C. Fig.16 of 1 The H-NMR results were basically consistent with the API, and no solvent residue was observed (there was a change in the NMR signal). In summary, it is speculated that Form E is an anhydrous form. In addition, Fig.17 As shown, the obtained crystal form E was heat-treated and heated to 230°C (the first line from bottom to top) and 260°C (the second line from bottom to top) respectively under nitrogen protection. After XRPD (the third line from bottom to top) of the heat-treated crystal form E was detected, it was found that Fig.17 It can be seen that the crystal form E remains unchanged after heat treatment at 230°C, but transforms into crystal form J after heating to 260°C (the fourth line from the bottom).

[0170] Comparative Example 2

[0171] The preparation method of the OAB-14 crystal form E is as follows: take 0.1 g of OAB-14, then add 20 ml of acetone / water (volume ratio 1:1), perform gas-solid diffusion at 10° C., keep warm and stir for 5 days, filter, and dry to obtain 0.09 g of OAB-14 crystal form E.

[0172] Comparative Example 3

[0173] The preparation method of the OAB-14 crystal form E is as follows: 0.2 g of OAB-14 is taken, 20 ml of acetone is added, gas-solid diffusion is performed at 20° C., the mixture is stirred at this temperature for 1 day, filtered, and dried to obtain 0.18 g of OAB-14 crystal form E.

[0174] Comparative Example 4

[0175] The preparation method of the OAB-14 crystal form F is as follows: take 0.2g of OAB-14, then add 20ml DMSO, then cycle the temperature up and down at 10°C-30°C-10°C, slurry for 2h and then filter, and naturally dry to obtain 0.18g of OAB-14 crystal form F.

[0176] Comparative Example 5

[0177] The preparation method of the OAB-14 crystal form F is as follows: 0.3 g of OAB-14 is taken, 30 ml of DMSO is added, and the temperature is raised and lowered according to a cycle of 20°C to 40°C to 20°C, the mixture is slurried for 4 hours, and then filtered and dried naturally to obtain 0.29 g of OAB-14 crystal form F ( Fig. 20 The first one from the bottom up). It was fully characterized and the results are shown in Figure 18~Figure 20 The crystal form was vacuum dried ( Fig. 20 The third line from bottom to top) then transforms into crystal form O ( Fig. 20 The second line from the bottom), so no thermal analysis test was performed. Fig.18 The XRPD results showed that the sample had moderate crystallinity. Fig.19 of 1 The H-NMR result was basically consistent with the raw material, and 13.1% of DMSO solvent remained in the sample. In summary, the crystal form F is a transitional crystal form.

[0178] Comparative Example 6

[0179] The preparation method of the OAB-14 crystal form F is as follows: take 0.1 g of OAB-14, then add 10 ml of DMSO / water (volume ratio 1:1), then cycle the temperature from 30°C to 50°C to 30°C, slurry for 6 hours, filter, and naturally dry to obtain 0.08 g of OAB-14 crystal form F.

[0180] Comparative Example 7

[0181] The preparation method of the OAB-14 crystal form G is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of purified water is added, and the mixture is suspended, stirred and slurried. The temperature is then raised and lowered according to a cycle of 20°C to 40°C to 20°C, and the mixture is slurried for 3 days and then filtered and dried to obtain 0.18 g of OAB-14 crystal form G.

[0182] Comparative Example 8

[0183] The preparation method of the OAB-14 crystal form G is as follows: 0.3 g of OAB-14 is taken, then 30 ml of purified water is added, the mixture is suspended, stirred and slurried, and then the temperature is raised and lowered according to a cycle of 30°C to 50°C to 30°C, and after slurrying for 5 days, the mixture is filtered and dried to obtain 0.28 g of OAB-14 crystal form G. A comprehensive characterization was performed, and the results are shown in Figure 21~Figure 24 . Fig.21 The XRPD results showed that the sample had a high degree of crystallinity. Fig.23 The TGA results showed that the sample lost 3.49% weight when heated from room temperature to 100°C and lost 4.72% weight when heated to 250°C. The sample began to decompose around 375.9°C. Fig.23The DSC results showed that the sample had an endothermic peak near 379.3℃. Fig.24 of 1 The H-NMR results were basically consistent with the raw materials. The wet sample of Form G (obtained by filtration after 5 days of beating), the dry sample (obtained after drying), and the Fig. 22 The second sample from the bottom up) is compared with the XRPD of the sample, such as Fig. 22 As shown, wet sample ( Fig. 22 From bottom to top) XRPD after drying ( Fig. 22 The third line from the bottom up) changes around 18-19°, and then the dried sample is heated to 100°C, and the XRPD result remains unchanged. In summary, Form G is a hydrate.

[0184] Comparative Example 9

[0185] The preparation method of the OAB-14 crystal form G is as follows: take 0.2g of OAB-14, then add 20ml of purified water, suspend, stir and slurry, then cycle the temperature from 40°C to 60°C to 40°C, slurry for 7 days and then filter, and obtain 0.18g of OAB-14 crystal form G after drying.

[0186] Comparative Example 10

[0187] The preparation method of the OAB-14 crystal form H is as follows: take 0.2g of OAB-14, then add 20ml of N,N-dimethylformamide, then cycle the temperature from 20°C to 40°C to 20°C, slurry for 5 days, filter, and dry to obtain 0.19g of OAB-14 crystal form H.

[0188] Comparative Example 11

[0189] The preparation method of the OAB-14 crystal form H is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of N, N-dimethylformamide is added, and then the temperature is raised and lowered according to a cycle of 30°C~50°C~30°C, and then the pulping is performed for 7 days and then filtered, and 0.28 g of OAB-14 crystal form H is obtained after drying. It was fully characterized, and the results are shown in Figure 25~Figure 27 . XRPD results show that the sample has a high degree of crystallinity. TGA results show that the sample loses 2.15% weight when heated from room temperature to 100.0℃, and loses 11.75% weight when heated to 170℃. The sample begins to decompose at around 385.3℃. DSC results show that the sample has endothermic peaks at around 147.4℃ and 389.6℃. 1 The H-NMR results were basically consistent with the raw material, and 12.4% of N,N-dimethylformamide solvent remained in the sample. In summary, Form H is an N,N-dimethylformamide solvate.

[0190] Comparative Example 12

[0191] The preparation method of the OAB-14 crystal form H is as follows: take 0.2g of OAB-14, then add 20ml of N,N-dimethylformamide, then cycle the temperature from 40°C to 60°C to 40°C, slurry for 9 days, filter, and dry to obtain 0.18g of OAB-14 crystal form H.

[0192] Comparative Example 13

[0193] The preparation method of the OAB-14 crystal form I is as follows: take 0.2g of OAB-14, then add 20ml of N-methylpyrrolidone, then cycle the temperature from 30°C to 40°C to 30°C, slurry for 3 days, filter, and dry to obtain 0.18g of OAB-14 crystal form I.

[0194] Comparative Example 14

[0195] The preparation method of the OAB-14 crystal form I is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of N-methylpyrrolidone is added, and then the temperature is raised and lowered according to a cycle of 40°C~50°C~40°C, and then the pulping is performed for 5 days and then filtered, and 0.29 g of OAB-14 crystal form I is obtained after drying. It was fully characterized, and the results are shown in Figure 28~Figure 31 . XRPD results show that the sample has high crystallinity. TGA results show that the sample loses 2.29% weight when heated from room temperature to 100.0℃, and loses 20.53% weight when heated to 235.0℃. The sample begins to decompose around 367.8℃. DSC results show that the sample has endothermic peaks around 211.4℃ and 369.3℃. 1 The H-NMR results were basically consistent with the raw material, and 8.04% of N-methylpyrrolidone solvent remained in the sample. In summary, it is speculated that Form I is a solvate of N-methylpyrrolidone. In addition, Form I ( Fig.31 From the bottom to the top, the first line) was heated to 230°C under nitrogen protection ( Fig. 22 The second line from bottom to top) transforms into crystal form J ( Fig.31 The third one from the bottom).

[0196] Comparative Example 15

[0197] The preparation method of the OAB-14 crystal form I is as follows: take 0.2g of OAB-14, then add 20ml of N-methylpyrrolidone, then cycle the temperature from 50°C to 60°C to 50°C, slurry for 7 days, filter, and dry to obtain 0.17g of OAB-14 crystal form I.

[0198] Comparative Example 16

[0199] The preparation method of the OAB-14 crystal form J is as follows: 20 mg of crystal form W (prepared in Comparative Example 53) is taken, and the temperature is heated to 200° C. and kept warm for 5 minutes under nitrogen protection to obtain 19.5 mg of OAB-14 crystal form J.

[0200] Comparative Example 17

[0201] The preparation method of the OAB-14 crystal form J is as follows: 20 mg of crystal form W (crystal form W is prepared in Example 53) is taken, and the temperature is heated to 250° C. and kept warm for 10 minutes under nitrogen protection to obtain 19.2 mg of OAB-14 crystal form J. The sample of the crystal form J has a low crystallinity and is insoluble in deuterated DMSO and deuterated methanol, so it is not subjected to NMR testing. The XRPD of the sample of the crystal form J is as follows Fig.32 shown.

[0202] Comparative Example 18

[0203] The preparation method of the OAB-14 crystal form J is as follows: take 20 mg of crystal form W (crystal form W is prepared in Example 53), heat to 300° C. under nitrogen protection and keep warm for 15 minutes to obtain 19.0 mg of OAB-14 crystal form J.

[0204] Comparative Example 19

[0205] The preparation method of the OAB-14 crystal form K is as follows: take 20 mg of crystal form L (crystal form L is prepared in Example 23), heat to 200° C. under nitrogen protection and keep warm for 5 minutes to obtain 19.7 mg of OAB-14 crystal form K.

[0206] Comparative Example 20

[0207] The preparation method of the OAB-14 crystal form K is as follows: 20 mg of crystal form L (crystal form W is prepared in Example 23) is taken, and the temperature is heated to 250° C. and kept warm for 10 minutes under nitrogen protection to obtain 19.5 mg of OAB-14 crystal form K. XRPD, 1 H-NMR characterization, the results are shown in Figure 33~Figure 34 The XRPD results showed that the sample had moderate crystallinity. 1 The H-NMR result is basically consistent with the raw material. In summary, the crystal form K is anhydrous crystal form.

[0208] Comparative Example 21

[0209] The preparation method of the OAB-14 crystal form K is as follows: take 20 mg of crystal form L (crystal form W is prepared in Example 23), heat to 300° C. under nitrogen protection and keep warm for 15 minutes to obtain 19.1 mg of OAB-14 crystal form K.

[0210] Comparative Example 22

[0211] The preparation method of the OAB-14 crystal form L is as follows: take 0.2 g of OAB-14, then add 20 ml of acetone, suspend and slurry at 0° C., keep warm and stir for 3 days, filter, and dry to obtain 0.19 g of OAB-14 crystal form L.

[0212] Comparative Example 23

[0213] The preparation method of the OAB-14 crystal form L is as follows: 0.3 g of OAB-14 is taken, then 30 ml of acetone is added, the mixture is suspended and slurried at 5°C, the mixture is stirred for 5 days, and then filtered and dried to obtain 0.28 g of OAB-14 crystal form L. A comprehensive characterization was performed on the mixture, and the results are shown in Figure 35~Figure 38 The XRPD results showed that the sample had a moderate degree of crystallinity. The TGA results showed that the sample lost 2.39% weight when heated from room temperature to 100°C, and the sample began to decompose at around 357.8°C. The DSC results showed that there was an endothermic peak at around 362.2°C. 1 The H-NMR results are basically consistent with the raw material (there are changes in the NMR signal). Fig.38 From bottom to top) After stirring at room temperature for 7 days ( Fig.38 The second line from the bottom), the crystal form did not change, but after heating to 200 ° C and keeping it for 7 days, it turned into crystal form K ( Fig.38 The third one from the bottom up). In summary, there is no crystalline form L.

[0214] Comparative Example 24

[0215] The preparation method of the OAB-14 crystal form L is as follows: take 0.2g of OAB-14, then add 20ml of acetone, suspend and slurry at 10°C, keep warm and stir for 7 days, filter, and dry to obtain 0.18g of OAB-14 crystal form L.

[0216] Comparative Example 25

[0217] The preparation method of the OAB-14 crystal form M is as follows: take 0.2 g of OAB-14, then add 20 ml of butanone, suspend and slurry at 0° C., keep warm and stir for 1 day, filter, and dry to obtain 0.19 g of OAB-14 crystal form M.

[0218] Comparative Example 26

[0219] The preparation method of the OAB-14 crystal form M is as follows: 0.3 g of OAB-14 is taken, then 30 ml of butanone is added, the mixture is suspended and slurried at 5°C, and the mixture is stirred for 3 days. After filtration and drying, 0.29 g of OAB-14 crystal form M is obtained. XRPD and NMR characterization are performed on the crystal form M, and the results are shown in Figure 39~Figure 41 The XRPD results showed that the sample had moderate crystallinity.1 The H-NMR results were basically consistent with the raw material, and 12.2% of butanone solvent remained in the sample. In summary, Form M is a transitional form.

[0220] Comparative Example 27

[0221] The preparation method of the OAB-14 crystal form M is as follows: 0.2 g of OAB-14 is taken, 20 ml of butanone is added, the mixture is suspended and slurried at 10° C., the mixture is stirred and kept warm for 5 days, and the mixture is filtered and dried to obtain 0.18 g of OAB-14 crystal form M.

[0222] Comparative Example 28

[0223] The preparation method of the OAB-14 crystal form M is as follows: 0.2 g of OAB-14 is taken, 20 ml of acetonitrile is added, the mixture is suspended and slurried at 0° C., the mixture is stirred and kept warm for 5 days, and the mixture is filtered and dried to obtain 0.17 g of OAB-14 crystal form N.

[0224] Comparative Example 29

[0225] The preparation method of the OAB-14 crystal form N is as follows: 0.3 g of OAB-14 is taken, then 30 ml of acetonitrile is added, the mixture is suspended and slurried at 5°C, the mixture is stirred for 7 days, and then filtered and dried to obtain 0.28 g of OAB-14 crystal form N. The crystal form N was fully characterized, and the results are shown in Figure 42~Figure 45 . XRPD results show that the sample has medium crystallinity. TGA results show that the sample loses 1.41% weight when heated from room temperature to 100°C, loses 8.86% weight when heated to 200.0°C, and loses 5.62% weight when heated to 270.0°C. The sample begins to decompose near 358.8°C. DSC results show that the sample has endothermic peaks near 182.8°C, 243.0°C, and 362.1°C. 1 The H-NMR results were basically consistent with the raw material, and 3.6% of acetonitrile solvent remained in the sample. In summary, it is speculated that Form N is an acetonitrile solvate. In addition, Form N ( Fig.45 From bottom to top) After stirring at room temperature for 7 days ( Fig.45 The second line from the bottom), the crystal form did not change, but after heating to 200 ° C and keeping it for 3 days, it turned into crystal form D ( Fig.45 The third one from the bottom).

[0226] Comparative Example 30

[0227] The preparation method of the OAB-14 crystal form N is as follows: take 0.2 g of OAB-14, then add 20 ml of acetonitrile, suspend and slurry at 10° C., keep warm and stir for 9 days, filter, and dry to obtain 0.17 g of OAB-14 crystal form N.

[0228] Comparative Example 31

[0229] The preparation method of the OAB-14 crystal form O is as follows: 0.2 g of OAB-14 is taken, 20 ml of dimethyl sulfoxide is added, the mixture is suspended and slurried at 100° C., the mixture is stirred and kept warm for 1 day, filtered, and dried to obtain 0.18 g of OAB-14 crystal form O.

[0230] Comparative Example 32

[0231] The preparation method of the OAB-14 crystal form O is as follows: 0.3 g of OAB-14 is taken, then 30 ml of dimethyl sulfoxide is added, the mixture is suspended and slurried at 120°C, the mixture is stirred for 3 days, and then filtered and dried to obtain 0.28 g of OAB-14 crystal form O. The crystal form O was fully characterized, and the results are shown in Figure 46~Figure 48 . XRPD results show that the sample has a high degree of crystallinity. TGA results show that the sample loses 0.76% weight when heated from room temperature to 100°C, and loses 14.17% weight when heated to 210.0°C. The sample begins to decompose at around 371.2°C. DSC results show that the sample has an endothermic peak at around 198.5°C and an endothermic peak at around 375.9°C. 1 The H-NMR results were basically consistent with those of the raw material, and 13.9% of DMSO solvent remained in the sample. In summary, it was inferred that Form O was a dimethyl sulfoxide solvate.

[0232] Comparative Example 33

[0233] The preparation method of the OAB-14 crystal form O is as follows: take 0.2g of OAB-14, then add 20ml of dimethyl sulfoxide, suspend and slurry at 140°C, keep warm and stir for 5 days, filter, and dry to obtain 0.17g of OAB-14 crystal form O.

[0234] Comparative Example 34

[0235] The preparation method of the OAB-14 crystal form P is as follows: take 0.2g of OAB-14, then add 20ml of N-methylpyrrolidone, perform gas-solid dispersion at 0°C, keep warm and stir for 5 days, filter, and dry to obtain 0.17g of OAB-14 crystal form P.

[0236] Comparative Example 35

[0237] The preparation method of the OAB-14 crystal form P is as follows: 0.3 g of OAB-14 is taken, then 30 ml of N-methylpyrrolidone is added, gas-solid dispersion is performed at 5°C, the mixture is stirred for 7 days, filtered, and dried to obtain 0.27 g of OAB-14 crystal form P. A comprehensive characterization was performed on the crystal form P, and the results are shown in Figure 49~Figure 51. XRPD results show that the sample has a high degree of crystallinity. TGA results show that the sample loses 4.50% weight when heated from room temperature to 100°C, and loses 17.36% weight when heated to 212.0°C. The sample begins to decompose around 375.4°C. DSC results show that the sample has endothermic peaks around 197.5°C and 376.3°C. 1 The H-NMR result was basically consistent with the raw material, and 8.0% of N-methylpyrrolidone solvent remained in the sample. In summary, Form P is an N-methylpyrrolidone solvate.

[0238] Comparative Example 36

[0239] The preparation method of the OAB-14 crystal form P is as follows: take 0.2g of OAB-14, then add 20ml of N-methylpyrrolidone, perform gas-solid dispersion at 10°C, keep warm and stir for 9 days, filter, and dry to obtain 0.17g of OAB-14 crystal form P.

[0240] Comparative Example 37

[0241] The preparation method of the OAB-14 crystal form Q is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 2-methyltetrahydrofuran is added, and the mixture is suspended and slurried at 20° C., and stirred for 5 days at this temperature. After suction filtration and drying, 0.18 g of OAB-14 crystal form Q is obtained.

[0242] Comparative Example 38

[0243] The preparation method of the OAB-14 crystal form Q is as follows: 0.3 g of OAB-14 is taken, then 30 ml of 2-methyltetrahydrofuran is added, suspended and slurried at 40°C, stirred for 7 days, filtered, and dried to obtain 0.28 g of OAB-14 crystal form Q. It was fully characterized, and the results are shown in Figure 52~Figure 54 . XRPD results show that the sample has medium crystallinity. TGA results show that the sample loses 2.07% weight when heated from room temperature to 100°C, and loses 9.27% ​​weight when heated to 160.0°C. The sample begins to decompose around 318.2°C. DSC results show that the sample has endothermic peaks at 150.8°C and 314.9°C. 1 The H-NMR result was basically consistent with that of the raw material, and 7.1% of 2-methyltetrahydrofuran solvent remained in the sample. In summary, Form Q is a 2-methyltetrahydrofuran solvate.

[0244] Comparative Example 39

[0245] The preparation method of the OAB-14 crystal form Q is as follows: 0.2 g of OAB-14 is taken, 20 ml of 2-methyltetrahydrofuran is added, the mixture is suspended and slurried at 60° C., the mixture is stirred and kept warm for 9 days, and the mixture is filtered and dried to obtain 0.17 g of OAB-14 crystal form Q.

[0246] Comparative Example 40

[0247] The preparation method of the OAB-14 crystal form R is as follows: 0.2 g of OAB-14 is taken, 20 ml of butanone is added, the mixture is suspended and slurried at 40° C., the mixture is stirred and kept warm for 1 day, filtered, and dried to obtain 0.19 g of OAB-14 crystal form R.

[0248] Comparative Example 41

[0249] The preparation method of the OAB-14 crystal form R is as follows: 0.3 g of OAB-14 is taken, then 30 ml of butanone is added, suspended and slurried at 50°C, stirred for 3 days, filtered, and dried to obtain 0.29 g of OAB-14 crystal form R. It was fully characterized, and the results are shown in Figure 55~Figure 58 . XRPD results show that the sample has a low degree of crystallinity. TGA results show that the sample loses 2.77% weight when heated from room temperature to 100°C, and loses 11.52% weight when heated to 210.0°C. The sample begins to decompose around 350.9°C. DSC results show that the sample has an endothermic peak around 353.4°C. 1 The H-NMR results were basically consistent with the raw material, and the sample showed 6.1% butanone solvent residue. In summary, Form R is a butanone solvate. In addition, Form R ( Fig.58 From bottom to top, the first line) is heated to 210℃ under nitrogen protection and transforms into crystal form J ( Fig.58 Second from bottom to top).

[0250] Comparative Example 42

[0251] The preparation method of the OAB-14 crystal form R is as follows: 0.2 g of OAB-14 is taken, 20 ml of butanone is added, the mixture is suspended and slurried at 60° C., the mixture is stirred and kept warm for 5 days, and the mixture is filtered and dried to obtain 0.19 g of OAB-14 crystal form R.

[0252] Comparative Example 43

[0253] The preparation method of the OAB-14 crystal form S is as follows: take 0.2 g of OAB-14, then add 20 ml of methanol, evaporate and crystallize at 15° C., filter, and dry to obtain 0.17 g of OAB-14 crystal form S.

[0254] Comparative Example 44

[0255] The preparation method of the OAB-14 crystal form S is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of methanol is added, evaporated and crystallized at 20°C, filtered, and dried to obtain 0.18 g of OAB-14 crystal form S. It was fully characterized, and the results are shown in Figure 59~Figure 61. XRPD results show that the sample has a medium degree of crystallinity. TGA results show that the sample loses 37.94% weight when heated from room temperature to 95°C, and the sample begins to decompose around 326.9°C. DSC results show that the sample has an endothermic peak at 78.0°C and an endothermic peak around 339.6°C. 1 The H-NMR result is basically consistent with the raw material. In summary, the crystal form S is a hydrate.

[0256] Comparative Example 45

[0257] The preparation method of the OAB-14 crystal form S is as follows: take 0.2 g of OAB-14, then add 20 ml of methanol, evaporate and crystallize at 25° C., filter, and dry to obtain 0.16 g of OAB-14 crystal form S.

[0258] Comparative Example 46

[0259] The preparation method of the OAB-14 crystal form T is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 1:1 (volume ratio) methanol and dichloromethane are added, and the mixture is rapidly evaporated and crystallized at 40° C., and then filtered and dried to obtain 0.18 g of OAB-14 crystal form T.

[0260] Comparative Example 47

[0261] The preparation method of the OAB-14 crystal form T is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of 1:1 (volume ratio) methanol and dichloromethane are added, and the crystals are rapidly evaporated at 50°C, filtered, and dried to obtain 0.28 g of OAB-14 crystal form T. It was obtained by rapid evaporation in a methanol / dichloromethane (1:1) system and was fully characterized. The results are shown in Figure 62~Figure 64 The XRPD results showed that the sample had moderate crystallinity. 1 The H-NMR results were basically consistent with the raw materials, and no obvious solvent residue was found in the sample. TGA results showed that the sample lost 9.05% weight when heated from room temperature to 100°C, and the sample began to decompose around 351.2°C. DSC results showed that the sample had endothermic peaks around 90.5°C and 353.2°C. In summary, Form T is a hydrate.

[0262] Comparative Example 48

[0263] The preparation method of the OAB-14 crystal form T is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 1:1 (volume ratio) methanol and dichloromethane are added, and the mixture is rapidly evaporated and crystallized at 60° C., and then filtered and dried to obtain 0.17 g of OAB-14 crystal form T.

[0264] Comparative Example 49

[0265] The preparation method of the OAB-14 crystal form U is as follows: 0.2 g of OAB-14 is taken, 20 ml of ethanol is added, volatilization and crystallization are carried out at 15° C., suction filtration is performed, and 0.18 g of OAB-14 crystal form U is obtained after drying.

[0266] Comparative Example 50

[0267] The preparation method of the OAB-14 crystal form U is as follows: 0.3 g of OAB-14 is taken, then 30 ml of ethanol is added, evaporated and crystallized at 20°C, filtered, and dried to obtain 0.28 g of OAB-14 crystal form U. It is obtained by low-temperature evaporation in ethanol and is fully characterized. The results are shown in Figure 65~Figure 67 . XRPD results show that the sample has medium crystallinity. TGA results show that the sample loses 21.69% weight when heated from room temperature to 75°C, and the sample begins to decompose around 338.5°C. DSC results show that the sample has endothermic peaks around 67.1°C and 338.5°C. 1 The H-NMR results were basically consistent with those of the raw material, and no solvent residue was found in the sample. In summary, Form U is a hydrate.

[0268] Comparative Example 51

[0269] The preparation method of the OAB-14 crystal form U is as follows: 0.2 g of OAB-14 is taken, 20 ml of ethanol is added, volatilization and crystallization are carried out at 25° C., suction filtration is performed, and 0.18 g of OAB-14 crystal form U is obtained after drying.

[0270] Comparative Example 52

[0271] The preparation method of the OAB-14 crystal form V is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 2:1 (volume ratio) acetonitrile / water is added, evaporated and crystallized at 15° C., filtered, and dried to obtain 0.18 g of OAB-14 crystal form V.

[0272] Comparative Example 53

[0273] The preparation method of the OAB-14 crystal form V is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of 4:1 (volume ratio) acetonitrile / water is added, evaporated and crystallized at 20°C, filtered, and dried to obtain 0.28 g of OAB-14 crystal form V. XRPD is shown in Fig.68 The results show that the sample has a medium degree of crystallinity. In summary, Form V is a transition state.

[0274] Comparative Example 54

[0275] The preparation method of the OAB-14 crystal form V is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 6:1 (volume ratio) acetonitrile / water is added, evaporated and crystallized at 25° C., filtered, and dried to obtain 0.18 g of OAB-14 crystal form V.

[0276] Comparative Example 55

[0277] The preparation method of the OAB-14 crystal form V is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 3:1 (volume ratio) acetone / water is added, evaporated and crystallized at 40° C., filtered, and dried to obtain 0.18 g of OAB-14 crystal form W.

[0278] Comparative Example 56

[0279] The preparation method of the OAB-14 crystal form W is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of 4:1 (volume ratio) acetone / water is added, and the crystals are evaporated at 50°C, filtered, and dried to obtain 0.27 g of OAB-14 crystal form W. It is obtained by rapid evaporation in an acetone / water (4:1) system and is fully characterized. The results are shown in Figure 69~Figure 72 . XRPD results show that the sample has medium crystallinity. TGA results show that the sample loses 6.7% weight when heated from room temperature to 100°C, and the sample begins to decompose around 333.2°C. DSC results show that the sample has endothermic peaks around 225.1°C and 329.2°C. 1 The H-NMR results were basically consistent with the raw material, and 2.0% of acetone solvent remained in the sample. In summary, Form W is an acetone solvate. In addition, Form W ( Fig.72 The second one from the bottom) was heated to 230℃ under nitrogen protection ( Fig.72 The third line from bottom to top) transforms into crystal form J ( Fig.72 First item from bottom to top).

[0280] Comparative Example 57

[0281] The preparation method of the OAB-14 crystal form W is as follows: 0.2 g of OAB-14 is taken, and then 20 ml of 5:1 (volume ratio) acetone / water is added, evaporated and crystallized at 60° C., filtered, and dried to obtain 0.18 g of OAB-14 crystal form W.

[0282] Comparative Example 58

[0283] The preparation method of the OAB-14 crystal form X is as follows: 0.2 g of OAB-14 is taken, 20 ml of ethanol is added, and the mixture is rapidly evaporated and crystallized at 50° C., and then filtered and dried to obtain 0.18 g of OAB-14 crystal form X.

[0284] Comparative Example 59

[0285] The preparation method of the OAB-14 crystal form X is as follows: 0.3 g of OAB-14 is taken, then 30 ml of ethanol is added, and the crystal is rapidly evaporated at 60°C, filtered, and dried to obtain 0.28 g of OAB-14 crystal form X. It is obtained by the method of rapid evaporation in ethanol. The XRPD results are shown in Fig.73 The XRPD results show that the sample has a moderate degree of crystallinity. In summary, Form X is a transition state.

[0286] Comparative Example 60

[0287] The preparation method of the OAB-14 crystal form X is as follows: 0.2 g of OAB-14 is taken, 20 ml of ethanol is added, and the mixture is rapidly evaporated and crystallized at 70° C., and then filtered and dried to obtain 0.18 g of OAB-14 crystal form X.

[0288] Comparative Example 61

[0289] The preparation method of the OAB-14 crystal form Y is as follows: take 0.2g of OAB-14, then add 20ml of 3:1 (volume ratio) acetone / water, dissolve it at 50°C, cool it at a cooling rate of 5°C / min to rapidly crystallize it, filter it, and dry it to obtain 0.18g of OAB-14 crystal form Y.

[0290] Comparative Example 62

[0291] The preparation method of the OAB-14 crystal form Y is as follows: 0.3 g of OAB-14 is taken, and then 30 ml of 4:1 (volume ratio) acetone / water is added, dissolved at 60°C, and then rapidly cooled at a cooling rate of 10°C / min for crystallization, filtered, and dried to obtain 0.28 g of OAB-14 crystal form Y. It was obtained by rapid cooling in an acetone / water (4:1) system and was fully characterized. The results are shown in Figure 74~Figure 76 . XRPD results show that the sample has medium crystallinity. TGA results show that the sample loses 3.21% weight when heated from room temperature to 100°C, and loses 10.11% weight when heated to 230°C. The sample begins to decompose around 351.9°C. DSC results show that the sample has endothermic peaks around 207.9°C and 354.0°C. 1 The H-NMR result is inconsistent with the raw material, there are impurity peaks, and no obvious acetone solvent residue is found in the sample. In summary, the crystal form Y is an anhydrous crystal form.

[0292] Comparative Example 63

[0293] The preparation method of the OAB-14 crystal form Y is as follows: take 0.2g of OAB-14, then add 20ml of 5:1 (volume ratio) acetone / water, dissolve at 70°C, cool rapidly at a cooling rate of 15°C / min to crystallize, filter, and dry to obtain 0.18g of OAB-14 crystal form Y.

[0294] The OAB-14 crystal form B used in the following comparative examples was prepared by Shandong Xinhua Pharmaceutical Co., Ltd. with batch number QYST23-08-03.

[0295] Comparative Example 64

[0296] The preparation method of the OAB-14 crystal form Y is as follows: 20 mg of OAB-14 crystal form B is taken, and then placed under lighting (cold white light, 5000 Lux ± 500 Lux; closed) conditions for 3 days to obtain 19 mg of crystal form Z.

[0297] Comparative Example 65

[0298] The preparation method of the OAB-14 crystal form Z is as follows: 30 mg of OAB-14 crystal form B is taken and then placed under light (cold white light, 5000 Lux ± 500 Lux; closed) conditions for 5 days to obtain 29 mg of crystal form Z. The crystal form B was obtained by placing it under light conditions for 5 days and was fully characterized. The results are shown in Figure 77~Figure 79 The XRPD results showed that the sample had moderate crystallinity. 1 The H-NMR results are basically consistent with the raw materials. In summary, it is inferred that the crystal form Z is anhydrous crystal form. TGA results show that the sample loses 9.55% weight when heated from room temperature to 100°C, and loses 8.0% weight when heated to 250°C. The sample begins to decompose around 354.1°C. DSC results show that the sample has endothermic peaks around 69.2°C and 355.5°C. 1 The H-NMR result is basically consistent with the raw material. In summary, the crystal form Z is a hydrate.

[0299] Comparative Example 66

[0300] The preparation method of the OAB-14 crystal form Z is as follows: 20 mg of OAB-14 crystal form B is taken, and then placed under lighting (cold white light, 5000 Lux ± 500 Lux; closed) conditions for 7 days to obtain 19 mg of crystal form Z.

[0301] The test conditions for the different crystal forms prepared in the above examples and comparative examples are as follows:

[0302] (1) XRPD: The testing instrument is Rigaku Smart Lab SE, and the testing conditions are: X-ray tube current 40 mA, scanning range 3-40° (2θ), step length 0.02°, scanning speed 5° / min. Testing basis: Appendix IXF X-ray powder diffraction method of the People's Republic of China (Part II, 2010 edition).

[0303] (2) TGA: The testing instrument is NETZSCH STA449F3. Testing conditions: nitrogen, 50 mL / min, scanning program: 30-400 °C, heating rate: 10 °C / min, testing sample mass: 5 mg (alumina sample pan), testing basis: JY / T014-1996 General rules for thermal analysis methods.

[0304] (3) DSC: The detection instrument is NETZSCH STA449F3. The detection conditions are nitrogen, 50 mL / min, scanning program: 30-400 °C, heating rate: 10 °C / min, detection sample mass: 3 mg (alumina sample pan), and detection basis: JY / T014-1996 General rules for thermal analysis methods.

[0305] (4) 1 H-NMR: The detection instrument is a nuclear magnetic resonance spectrometer (JMTC-400 / 54 / JJ / YH), the detection conditions are: 400 MHz, deuterated DMSO dissolution.

[0306] (5) HPLC: Detection instrument: Waters ALLIANCE E2695, chromatographic column: XBridge® C18, 4.6×250 mm, 5 μm, column temperature: 40°C, mobile phase A is 0.04 mol / L ammonium acetate aqueous solution; mobile phase B is methanol, detection wavelength is 273 nm; gradient elution conditions (T / B%): 0 / 10%, 1 / 10%, 6 / 90%, 15 / 90%, 15.1 / 10%, 20 / 10%, flow rate is 1.0 mL / min, injection volume is 5 μL, diluent is methanol; T is elution time in min, B% indicates the volume percentage of mobile phase B, and mobile phase A is omitted, then the volume percentage of mobile phase A is the corresponding 100%-B%.

[0307] (6) DVS (Dynamic Vapor Sorption Instrument): The detection instrument is SMSDVS Intrinsic PLUS. Detection conditions: gradient mode, humidity program is 0%RH-95%RH-0%RH, gradient: 10%RH.

[0308] (7) Dissolution: The testing instrument is ZEN3700 and the particle size analyzer is RC806D dissolution tester.

[0309] (I) The crystal forms D, E, F, G, H, I, J, K, L, M, N, O, P, Q, R, S, T, U, V, W, X, Y, and Z prepared in Example 2, Comparative Example 1, Comparative Example 5, Comparative Example 8, Comparative Example 11, Comparative Example 14, Comparative Example 17, Comparative Example 20, Comparative Example 23, Comparative Example 26, Comparative Example 29, Comparative Example 32, Comparative Example 35, Comparative Example 38, Comparative Example 41, Comparative Example 44, Comparative Example 47, Comparative Example 50, Comparative Example 53, Comparative Example 56, Comparative Example 59, Comparative Example 62, and Comparative Example 65, as well as the prepared crystal forms A, B, and C, were subjected to DSC and TGA, and their respective conditions and results are shown in Table 2.

[0310] Table 2 Thermal analysis conditions and results of different crystal forms

[0311]

[0312] (ii) The crystal forms D and E prepared in Example 2 and Comparative Example 1, as well as the prepared crystal forms A, B, and C, were systematically characterized to examine the stability, water activity, solubility, mechanical stability, hygroscopicity, and solid-state stability of the anhydrous crystal forms, and the dissolution tests were performed on the crystal forms A, B, C, D, and E. And the crystal forms used in the following screening are: Example 2, Comparative Example 1, Comparative Example 5, Comparative Example 8, Comparative Example 11, Comparative Example 14, Comparative Example 17, Comparative Example 20, Comparative Example 23, Comparative Example 26, Comparative Example 29, Comparative Example 32, Comparative Example 35, Comparative Example 38, Comparative Example 41, Comparative Example 44, Comparative Example 47, Comparative Example 50, Comparative Example 53, Comparative Example 56, Comparative Example 59, Comparative Example 62, Comparative Example 65, respectively prepared crystal form D, crystal form E, crystal form F, crystal form G, crystal form H, crystal form I, crystal form J, crystal form K, crystal form L, crystal form M, crystal form N, crystal form O, crystal form P, crystal form Q, crystal form R, crystal form S, crystal form T, crystal form U, crystal form V, crystal form W, crystal form X, crystal form Y, crystal form Z, and prepared crystal form A, crystal form B, and crystal form C.

[0313] 1. Suspension competition experiment without crystals

[0314] Referring to the screening results, it can be seen that anhydrous crystalline forms A, B, D, E, L, Y, J, and K were obtained in the screening experiment. Suspension competition experiments were carried out on anhydrous crystalline forms A, B, D, E, L, Y, J, and K in different solvents to determine their stability. The specific operations and results are as follows: Equal amounts of crystalline forms A, B, D, E, L, Y, J, and K were suspended and slurried in ethanol, ethyl acetate, and n-heptane systems. The results are summarized in Tables 3 and Figure 112~Figure 113 The experimental results show that after 10 days of beating in ethanol, ethyl acetate and n-heptane systems, the samples of Forms A, B, D, E, L, Y, J and K were transformed into Form D. Therefore, under room temperature conditions, anhydrous Form D is more stable than Forms A, B, E, L, Y, J and K. Fig.112 This is a curve of a mixture of eight crystalline forms, namely, anhydrous crystalline forms A, B, D, E, L, Y, J, and K, mixed and stirred for 5 days in three solvents. From bottom to top, the solvents used are ethanol, ethyl acetate, and n-heptane, respectively. Fig.113 The curves are of a mixture of eight crystalline forms, namely, anhydrous crystalline forms A, B, D, E, L, Y, J, and K, mixed and stirred for 10 days in three solvents. From bottom to top, the solvents used are ethanol, ethyl acetate, and n-heptane, respectively.

[0315] Table 3 Suspension competition experiment between anhydrous crystalline types

[0316]

[0317] 2. Water activity experiment

[0318] Referring to the screening results, it can be seen that there are 6 kinds of hydrates obtained by conventional methods in the experiment, namely, crystal forms C, G, S, T, U, and Z. The water activity of the conversion between the hydrate crystal forms G, S, T, U and the anhydrous crystal forms A, B, D, E, L, and Y was studied.

[0319] Crystal forms A, B, D, E, G, L, S, T, U, and Y were slurried in ethanol solvents with different water activities. The results are shown in Tables 4 and Fig.96 The experimental results show that when the water activity is lower than 0.003, they all transform into Form D; when the water activity is higher than 0.23, they all transform into Form G. In summary, Form D is more stable when the water activity is lower than 0.003, and Form G is more stable when the water activity is higher than 0.23. Fig.96 The XRPD curves of the mixture of ten crystal forms A, B, D, E, G, L, S, T, U, and Y at different water activities are shown in Figure 1. From the bottom to the top, the water activities are 0.003, 0.23, 0.54, 0.77, and 0.92, respectively. The sixth line is the XRPD curve of crystal form D, and the seventh line is the XRPD curve of crystal form G.

[0320] Table 4 Suspension experiment of samples at different water activities

[0321]

[0322] 3. Solubility test in biological media and water

[0323] Select crystal forms A, B, D, and E for solubility testing. Take an appropriate amount of crystal form samples and shake them in biological media (FaSSIF, FeSSIF, and FaSSGF) and water at 37°C for 24 hours for solubility testing. Weigh 30 mg of sample into a sample bottle, and then add 3 mL of three media and water to form a suspension. All suspensions were shaken at 200 rpm at 37°C, and the filtrate was observed, sampled, and tested for solubility at 0.5, 2, and 24 hours. In addition, XRPD and pH tests were performed on the remaining solid samples and filtrate after 24 hours.

[0324] The solubility results showed that the solubility of crystal forms A, B, C, D and E in the biological media FaSSIF, FeSSIF and water was poor, and the 24h solubility was less than 20g / mL. The solubility of most samples tended to decrease with the increase of oscillation time. The solubility of crystal forms A, B, C, D and E in the biological medium FaSSGF was significantly improved, and the 24h solubility reached between 2000-5000g / mL.

[0325] The remaining solid after solubility testing of Forms A, B, C, D, and E was analyzed.

[0326] Crystalline Form A ( Fig.90 From bottom to top, the first and Fig.91 Upper part) in FaSSIF ( Fig.90 The third one from the bottom up), FeSSIF ( Fig.90 The fourth one from the bottom), 24 hours in water ( Fig.90 From the bottom to the top, XRPD remains unchanged; in FaSSGF ( Fig.90 In the second line from bottom to top), at 24h, the XRPD result is a new crystal form. 1 H-NMR( Fig.91 The results in the lower part show that the structure of the FaSSGF compound has changed, and it is speculated that the free base compound has become a salt.

[0327] Crystalline Form B ( Fig.92 From the bottom up, the first one) in FaSSIF ( Fig.92 The third line from the bottom) was placed in the medium for 24 hours, and the XRPD result was Form G ( Fig.92 6th from bottom to top); 24h in water ( Fig.92 The fifth line from the bottom), XRPD results are Form G; in FeSSIF medium for 24h ( Fig.92 The fourth line from the bottom), XRPD results are amorphous; 24h in FaSSGF ( Fig.92 The second line from the bottom), XRPD results show a new crystal form, and it is speculated that the free base compound is salted.

[0328] Form C ( Fig.93From bottom to top) in FaSSIF medium ( Fig.93 The third one from the bottom) and 24h in water ( Fig.93 From the bottom to the top, the fifth line), XRPD results are all Form G; in FeSSIF ( Fig.93 Fourth from bottom to top) and FaSSGF ( Fig.93 The second line from the bottom) was in the medium for 24 hours, and the XRPD result was amorphous.

[0329] Crystalline Form D Fig.94 From bottom to top) in FaSSIF medium ( Fig.94 The third one from the bottom) and 24h in water ( Fig.94 The fifth line from the bottom), XRPD results are Form D; in FeSSIF medium ( Fig.94 The fourth line from the bottom) changes to amorphous after 24 h; in FaSSGF medium ( Fig.94 In the second line from the bottom), at 24h, the XRPD result showed a new crystal form, and it was inferred that the free base compound was salted.

[0330] Crystalline Form E ( Fig.95 From the bottom to the top) in FaSSIF medium for 24 h ( Fig.95 The second line from the bottom), XRPD results show that it is crystalline form E; it transforms into amorphous form in FeSSIF medium for 24 hours ( Fig.95 The third one from the bottom); 24 hours in water ( Fig.95 The fifth line from the bottom), XRPD results are Form G; in FaSSGF medium for 24h ( Fig.95 The fourth line from the bottom), XRPD results show a new crystal form, and it is speculated that the free base compound is salted.

[0331] In summary, the solubility of crystal forms A, B, C, D, and E is relatively poor, but crystal forms D and E have relatively good stability in FaSSIF medium and water. The specific experimental results are shown in Table 5 and Figure 90~Figure 95 As shown:

[0332] Table 5 Solubility test results in biological media and water

[0333]

[0334] 4. Mechanical stability test

[0335] 4.1 Grinding stability test of crystal form A

[0336] 30 mg of Form A was placed in a mortar and manually ground for 1 min and 3 min before XRPD testing. Fig.102 As shown ( Fig.102The first line from bottom to top is unground; the second line from bottom to top is ground for 1 min; the third line from bottom to top is ground for 3 min). The experimental results show that Form A is Form D after manual grinding for 1 min and 3 min, but the crystallinity is reduced.

[0337] 4.2 Tableting stability test of Form A

[0338] 30 mg of Form A was placed under a pressure of 4 MPa and XRPD tests were performed after 1 min and 3 min. Fig.103 As shown ( Fig.103 The first line from bottom to top is no pressure; the second line from bottom to top is 4 MPa pressure for 1 min; the third line from bottom to top is 4 MPa pressure for 3 min). The experimental results show that the crystal form of Form A remains unchanged after 1 min and 3 min under 4 MPa pressure, but the crystallinity is slightly reduced.

[0339] 4.3 Grinding stability test of Form B

[0340] 30 mg of Form B (batch: QYST23-23-1) was placed in a mortar and manually ground for 1 min and 3 min before XRPD testing. Fig.104 As shown ( Fig.104 The first line from bottom to top is unground; the second line from bottom to top is ground for 1 min; the third line from bottom to top is ground for 3 min). The experimental results show that Form B basically transforms into amorphous after manual grinding for 1 min and 3 min.

[0341] 4.4 Tableting stability test of Form B

[0342] 30 mg of Form B (batch: QYST23-23-1) was placed under a pressure of 4 MPa and XRPD tests were performed after 1 min and 3 min. Fig.105 XRPD comparison of Form B (batch: QYST23-23-1) before and after tableting ( Fig.105 The first line from bottom to top is no pressure; the second line from bottom to top is 4 MPa pressure for 1 min; the third line from bottom to top is 4 MPa pressure for 3 min). The experimental results show that the crystal form and crystallinity of Form B remain basically unchanged after 1 min and 3 min under 4 MPa pressure.

[0343] 4.5 Grinding stability test of Form C

[0344] 30 mg of Form C (batch: Y2401306) was placed in a mortar and manually ground for 1 min and 3 min before XRPD testing. Fig.106 As shown ( Fig.106The first line from bottom to top is ungrinded; the second line from bottom to top is ground for 1 min; the third line from bottom to top is ground for 3 min). The experimental results show that Form C transforms into Form G after manual grinding for 1 min and 3 min.

[0345] 4.6 Tableting stability test of Form C

[0346] 30 mg of Form C (batch: Y2401306) was placed under a pressure of 4 MPa and XRPD tests were performed after 1 min and 3 min. Fig.107 As shown ( Fig.107 The first line from bottom to top is no pressure; the second line from bottom to top is 4 MPa pressure for 1 min; the third line from bottom to top is 4 MPa pressure for 3 min). The experimental results show that Form C transforms into Form G after 1 min and 3 min under 4 MPa pressure.

[0347] 4.7 Grinding stability test of crystal form D

[0348] 30 mg of Form D (batch: QYST23-19-1) was placed in a mortar and manually ground for 1 min and 3 min before XRPD testing. Fig.108 As shown ( Fig.108 The first line from bottom to top is not ground; the second line from bottom to top is ground for 1 min; the third line from bottom to top is ground for 3 min). The experimental results show that the crystal form of Form D remains unchanged after manual grinding for 1 min and 3 min, and the crystallinity tends to decrease.

[0349] 4.8 Tableting stability test of Form D

[0350] 30 mg of Form D (batch: QYST23-19-1) was placed under a pressure of 4 MPa and XRPD tests were performed after 1 min and 3 min. Fig.109 As shown ( Fig.109 The first line from bottom to top is no pressure; the second line from bottom to top is 4 MPa pressure for 1 min; the third line from bottom to top is 4 MPa pressure for 3 min). The experimental results show that the crystal form of Form D remains unchanged after 1 min and 3 min under 4 MPa pressure, but the crystallinity decreases.

[0351] 4.9 Grinding stability test of crystal form E

[0352] 30 mg of Form E (batch: QYST23-23-4) was placed in a mortar and manually ground for 1 min and 3 min before XRPD testing. Fig.110 As shown ( Fig.110The first line from bottom to top is not ground; the second line from bottom to top is ground for 1 min; the third line from bottom to top is ground for 3 min). The experimental results show that the crystal form of Form E remains unchanged after manual grinding for 1 min and 3 min, but the crystallinity decreases.

[0353] 4.10 Tableting stability test of Form E

[0354] 30 mg of Form E (batch: QYST23-23-4) was placed under a pressure of 4 MPa and XRPD tests were performed after 1 min and 3 min. Fig.111 As shown ( Fig.111 The first line from bottom to top is no pressure; the second line from bottom to top is 4 MPa pressure for 1 min; the third line from bottom to top is 4 MPa pressure for 3 min). The experimental results show that the crystal form of Form E is maintained after 1 min and 3 min under 4 MPa pressure, and the crystallinity is reduced.

[0355] In summary, Form A turns into Form D after grinding for 1min and 3min, and the crystal form remains unchanged for 3min under a pressure of 4MPa, but the crystallinity decreases slightly (this means that the crystal form does not change without grinding but only under pressure, and changes after grinding); Form B basically turns into amorphous after grinding for 1min and 3min, and the crystal form and crystallinity remain basically unchanged after 1min and 3min under a pressure of 4MPa (Form B is similar to Form A); Form C turns into Form G after grinding for 1min and 3min and under a pressure of 4MPa; Forms D and E remain unchanged after grinding for 1min and 3min and under a pressure of 4MPa, but the crystallinity tends to decrease. It can be seen that Form D and Form E have good mechanical stability.

[0356] 5. Hygroscopicity test

[0357] Crystal form A (batch number: Y2401308) was subjected to DVS test to investigate its hygroscopicity. The results are as follows: Figure 80-Figure 81 The DVS results show that the sample gained 0.099% weight at 95% RH and 0.077% weight at 80% RH, indicating that Form A has almost no hygroscopicity and the form remains unchanged before and after the DVS test ( Fig.81 The upper part is the XRPD image of Form A before DVS testing, and the lower part is the XRPD image of Form A after DVS testing).

[0358] Crystal form B (batch number: QYST23-23-1) was subjected to DVS test to investigate its hygroscopicity. The results are as follows: Figure 82-Figure 83 The DVS results show that the sample gained 2.175% weight at 95% RH and 1.869% weight at 80% RH, indicating that Form B is slightly hygroscopic and the form remains unchanged before and after the DVS test ( Fig.83The lower part is the XRPD image of Form B before DVS testing, and the upper part is the XRPD image of Form B after DVS testing).

[0359] Crystal form C (batch number: Y2401306) was subjected to DVS test to investigate its hygroscopicity. The results are as follows: Figure 84-Figure 85 The DVS results show that the sample weight increased by 0.392% from 50%-95%RH, and by 0.212% from 50% to 80%RH, indicating that Form C is slightly hygroscopic. In addition, after the DVS test, the sample turned into Form G ( Fig.85 The XRPD image of Form C before DVS testing is shown below, and the XRPD image of Form C after DVS testing is shown above).

[0360] Crystal form D (batch number: QYST23-19-1) was subjected to DVS test to investigate its hygroscopicity. The results are as follows: Figure 86-Figure 87 The DVS results show that the sample gained 0.566% weight at 95% RH and 0.383% weight at 80% RH, indicating that the crystal form D is slightly hygroscopic and the crystal form remains unchanged before and after the DVS test ( Fig.87 The lower part is the XRPD image of Form D before DVS testing, and the upper part is the XRPD image of Form D after DVS testing).

[0361] Crystal form E (batch number: QYST23-23-4) was subjected to DVS test to investigate its hygroscopicity. The results are as follows: Figure 88-Figure 89 The XRPD comparison of Form E (batch: QYST23-23-4) before and after the DVS test is shown. The DVS results show that the sample gained 3.079% weight at 95% RH and 0.593% weight at 80% RH, indicating that Form E is slightly hygroscopic, and the XRPD of Form E after the DVS test showed a multi-peak phenomenon ( Fig.89 The upper part is the XRPD image of Form E before DVS testing, and the lower part is the XRPD image of Form E after DVS testing).

[0362] In summary, in terms of hygroscopicity, crystal form A is almost non-hygroscopic; crystal forms B, C, D, and E are slightly hygroscopic.

[0363] 6. Solid-state stability experiment

[0364] 30 mg of crystal forms A (batch: Y2401308), B (batch number: QYST23-23-1), C, D, and E were placed under 60°C (closed) illumination (cold white light, 5000Lux±500Lux; closed) and 25°C / 90%RH (open) for 5 days and 10 days respectively. The solid samples after placement were tested by XRPD and HPLC to analyze the crystal stability and chemical stability.

[0365] The results showed that under the conditions of light, high humidity and high temperature for 10 days, the crystal forms of crystal forms A, D and E did not change significantly, but the purity decreased, and slight degradation may have occurred; crystal form B was transformed into a new crystal form named crystal form Z under the conditions of light for 5 days and 10 days, and was partially transformed into crystal form Z under high humidity conditions. The purity of crystal form B decreased under the three conditions, and slight degradation may have occurred; crystal form C was transformed into crystal form G under the conditions of light, high temperature and high humidity for 5 days and 10 days, and the purity remained basically unchanged. The specific experimental results are shown in Table 6 and Figure 97~Figure 101 shown.

[0366] (1) Fig.97 This is a graph related to the stability experiment of Form A. From bottom to top, the first condition is no condition; the second condition is 25°C & 90% RH, 5 days; the third condition is 60°C, 5 days; the fourth condition is light, 5 days; the fifth condition is 25°C & 90% RH, 10 days; the sixth condition is 60°C, 10 days; the seventh condition is light, 10 days;

[0367] (2) Fig.98 This is a graph related to the stability experiment of Form B, where, from bottom to top, the first condition is no condition; the fourth condition is 25°C & 90% RH, 5 days; the second condition is 60°C, 5 days; the third condition is light, 5 days; the fifth condition is 25°C & 90% RH, 10 days; the sixth condition is 60°C, 10 days; the seventh condition is light, 10 days;

[0368] (3) Fig.99 This is a graph related to the stability experiment of Form C. From bottom to top, the first condition is no condition; the third condition is 25°C & 90% RH, 5 days; the second condition is 60°C, 5 days; the fourth condition is light, 5 days; the sixth condition is 25°C & 90% RH, 10 days; the fifth condition is 60°C, 10 days; the seventh condition is light, 10 days;

[0369] (4) Fig.100 This is a graph related to the stability experiment of crystal form D, where, from bottom to top, the first condition is no condition; the second condition is 25℃&90%RH, 5 days; the third condition is 60℃, 5 days; the fourth condition is light, 5 days; the fifth condition is 25℃&90%RH, 10 days; the sixth condition is 60℃, 10 days; the seventh condition is light, 10 days;

[0370] (5) Fig.101 This is a graph related to the stability experiment of Form E. From bottom to top, the first condition is no condition; the second condition is 25°C & 90% RH, 5 days; the third condition is 60°C, 5 days; the fourth condition is light, 5 days; the sixth condition is 25°C & 90% RH, 10 days; the fifth condition is 60°C, 10 days; the seventh condition is light, 10 days;

[0371] Table 6 XRPD and HPLC results of stability samples

[0372]

[0373] 7. Dissolution test

[0374] The dissolution results of different crystalline powders are shown in Table 7. The overall dissolution of crystal forms B, C, and D is similar, while that of crystal forms A and E is slightly slower. Crystal A may have a slightly slower overall dissolution due to its clumping; the slow dissolution of crystal E may be due to its poor wettability, with more powder floating on the liquid surface. However, the dissolution rate after 60 to 90 minutes has a clear advantage for crystal form D. The dissolution rate comparison is shown in Table 7.

[0375] Table 7 Comparison of dissolution of crystal forms A, B, C, D, and E

[0376]

[0377] In summary, at room temperature, anhydrous crystalline form D is more stable than crystalline forms A, B, E, L, Y, J, and K; crystalline form D is relatively stable when the water activity is lower than 0.003; crystalline form D and crystalline form E have relatively good stability in FaSSIF medium and water; crystalline form D and crystalline form E have good mechanical stability; crystalline forms B, C, D, and E are slightly hygroscopic; after 10 days under light, high humidity and high temperature conditions, the crystal forms A, D, and E did not undergo significant changes, but the purity decreased; in terms of dissolution after 60 to 90 minutes, crystalline form D has a clear advantage; considering all factors, we selected crystalline form D as the dominant crystalline form and continue with subsequent research.

Claims

1. A method for preparing form D of OAB-14, characterized in that: Add OAB-14 to the solvent, suspend and slurry, keep warm and stir, filter and dry to obtain crystal form D; the OAB-14 is crystal form A; The mixing and beating temperature is 15-25°C; The time of heat preservation and stirring is 1 to 5 days; The obtained OAB-14 crystal form D: the reflection angle 2θ of the X-ray powder diffraction pattern has characteristic peaks at 7.0252°, 9.7125°, 18.1961°, and 19.4787°, and the intensities thereof are 33.39%, 69.65%, 52.48%, and 100.00%, respectively; The solvent is one of tetrahydrofuran, methanol, ethanol, ethyl acetate and methyl tert-butyl ether.

2. The method for preparing the crystal form D of OAB-14 according to claim 1, characterized in that: After the OAB-14 is added to the solvent, the concentration of OAB-14 is 0.005 g / mL to 0.01 g / mL.

3. The method for preparing the crystalline form D of OAB-14 according to claim 1, characterized in that: The drying temperature is 60-80°C and the drying time is 6h-8h.

4. The method for preparing the crystal form D of OAB-14 according to claim 1, characterized in that: The OAB-14 is in the form A, with a content of 99.30%.

Citation Information

Patent Citations

  • Crystal form A of OAB-14 and preparation method thereof

    CN113896659A

  • Crystal form B of OAB-14 and preparation method thereof

    CN116924941A

  • Octahydro-anthracene compound and preparation method and application thereof

    CN107304172A